Perancangan Visual Brand Communication Kota Singkawang - Febry Valiansyah; Atria Nuraini Fadilla (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
Tourism industry is one of the most effective sectors in increasing the foreign exchange in Indonesia along with regional autonomy system that encourages to develop their economy independently. Blessed with a big tourism potential, Singkawang is still unrecognized for its tourism due to weak brand communication. This research used interview, literature review, questionnaire, and observations as data collection, also applied questionnaire analysis, comparison matrix analysis, SWOT analysis to analyze the collected data. The collected data was used as a reference to design brand communication of Singkawang City. The collected data showed that Singkawang needed to re-brand and improve promotion strategies, with lively diversity as a brand proposition and lively singkawang as a brand name. The visual aspect used cultural elements of Singkawang with a modern touch applied to logo and media promotions. The results of this research are to support the Tourism program and increase public awareness about Singkawang tourism. Keywords: Singkawang, Brand communication,Tourism